PENINGKATAN KUALITAS PEREMPUAN MELALUI PEMANFAATAN MEDIA MASSA - Erwin Kartinawati; Andrik Purwasito; Annisa Indah Mutiasari; Erna Indriastiningsih (LPPM Universitas Al Muslim, 2023)
Indonesian society, especially in Java, still places women in a subordinate position. Women are placed in three functions, namely macak, cook, and manak. As a result, women become less developed even though they have great potential to support regional and national development. This journalism training was held in order to empower the role of women so that they are not always placed in domestic tasks. It is time for women to show their existence through positive things. One of them is by productively writing or creating media content. This service activity is aimed at Nasyiatul Aisyiyah Boyolali Central Java cadres, an organization that focuses on empowering women. This activity was carried out through three stages, namely the delivery of material, practice, and evaluation. The material presented was about the mass media and the power they have as well as an understanding of the need to utilize the power of the mass media through mastering skills in making media products. At the practical stage, exercises were carried out on making journalistic scripts, photos and videos, then at the final stage was an evaluation of the work produced by the participants. The results of this service activity showed an increase in the quality of women through mastery of knowledge and skills in making journalistic scripts, photos and videos.